2016
DOI: 10.1101/gad.291021.116
|View full text |Cite
|
Sign up to set email alerts
|

PDX1 dynamically regulates pancreatic ductal adenocarcinoma initiation and maintenance

Abstract: Aberrant activation of embryonic signaling pathways is frequent in pancreatic ductal adenocarcinoma (PDA), making developmental regulators therapeutically attractive. Here we demonstrate diverse functions for pancreatic and duodenal homeobox 1 (PDX1), a transcription factor indispensable for pancreas development, in the progression from normal exocrine cells to metastatic PDA. We identify a critical role for PDX1 in maintaining acinar cell identity, thus resisting the formation of pancreatic intraepithelial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 54 publications
10
96
1
2
Order By: Relevance
“…In contrast to the indispensable role of Pdx1 in the formation of acinar cells during embryonic stages , Pdx1 depletion in half of the adult acinar cell mass did not cause any apparently abnormal macroscopic phenotypes; the pancreatic size looked normal, which is consistent with a previous report , and the mutant mice did not become lean or show fatty stools or diarrhea. Though Pdx1ā€depleted cells expressed decreased amounts of digestive enzymes such as amylase (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to the indispensable role of Pdx1 in the formation of acinar cells during embryonic stages , Pdx1 depletion in half of the adult acinar cell mass did not cause any apparently abnormal macroscopic phenotypes; the pancreatic size looked normal, which is consistent with a previous report , and the mutant mice did not become lean or show fatty stools or diarrhea. Though Pdx1ā€depleted cells expressed decreased amounts of digestive enzymes such as amylase (Fig.…”
Section: Resultssupporting
confidence: 90%
“…model [7], suggesting the involvement of Pdx1 in adult exocrine pancreas homeostasis. Furthermore, Roy et al [8] reported that the combination of Pdx1 inactivation and cerulein-induced pancreatitis causes apoptosis and a reduction in pancreatic mass. However, they also found that Pdx1 depletion in adult acinar cells does not cause a reduction in the amount of exocrine tissue in the absence of pancreatitis.…”
Section: Abstract: Acinar Cell; Pdx1; Senescencementioning
confidence: 99%
“…Lastly we sought to gain insight into the transcriptional activity of HNF1A in PDA and determine whether its transcriptome held prognostic information similar to other signatures in PDA (Bailey et al, 2016, Collisson et al, 2011. In order to identify transcriptional targets of HNF1A, we performed Bru-seq, a variation of RNA-seq which measures changes in nascent RNA levels (bone fide transcription rate) as opposed to steady-state RNA changes measured by conventional RNA-seq and microarray (Paulsen et al, 2013).…”
Section: An Hnf1a Gene Signature Is Associated With Poor Survival Inmentioning
confidence: 99%
“…3A). Since NR5A2 and PDX1 function in pancreatic acinar differentiation and are reportedly linked to PDA initiation and growth 19,40 , we asked whether RNF125 is involved in their regulation also in PDA. RNF125 expression was associated with the expression of both PDX1 and NR5A2 in normal pancreas (Fig.…”
Section: Rnf125 Controls Pda Growth Via Differential Regulation Of Pdx1mentioning
confidence: 99%